The Center for Research on Extreme Batteries. (1st January 2016) - Wachsman, Eric; Lundgren, Cynthia; Takeuchi, Esther; Xu, Kang; Wang, Chunsheng; Dura, Joseph; Jacobson, David; Amine, Kahlil; Acker, William
Abstract : The Center for Research on Extreme Batteries is introduced in this article. CREB, as it is abbreviated, was launched in late 2014 and is located on the campus of University of Maryland, College Park. It addresses various energy storage needs in extreme conditions, such as the demands of energy storage required by the Department of Defense (Soldier Power, Mobile Power, and Local Grids), energy storage for future space missions, where extreme temperatures, high levels of radiation, and decades of reliability are to be considered, and also battery power for implantable devices.